FORMATION OF THE UKRAINIAN RELIGIOUS AND ETHICAL LEXICON IN THE 16TH AND 17TH CENTURIES (Based on the Epistle to Galatians) - LEVKO, Oleksandr (Linguistic and Conceptual Worldviews, 2023)
The article explores the origins of the Ukrainian language ethical lexicon in biblical written monuments of the early modern period. It traces the rendition of the vices and virtues catalog in the Epistle to the Galatians (Gal. 5:19-23) in the Krekhiv Apostle, a manuscript of the 2nd half of the 16th century, in comparison with the Church Slavonic Ostroh Bible of 1581, as well as lexicographical works of the 17th century, in particular Pamva Berynda's "Lexicon", and Ukrainian translations of the Bible of the 19th and 20th centuries.The Epistle to the Galatians contains one of the most extensive New Testament catalogs of ethical values/anti-values. The vices and virtues in Gal. 5:19-23 form axiological oppositions, which indicate the values of verbal, emotional, behavioral, and social interaction between members of society.The Krekhiv Apostle uses Old Ukrainian and Church Slavonic words to nominate virtues and vices in the Epistle to the Galatians. More than half of the words in the ethical catalog of Gal. 5:19-23 in the Krekhiv Apostle differ from the usage of the Ostroh Bible. Most of these words are indicated as belonging to the "prosta mova" in lexicographical works of the 17th century, in particular in Pamva Berynda's "Lexicon". Two thematic subgroups of ethical vocabulary denoting vices in Gal. 5:19-21, namely vices of the corporal and emotional-volitional spheres, show a high level of variability in usage of the Old Ukrainian words instead of Church Slavonicisms in written monuments of the early modern period.Ukrainian biblical translations of the 19th and 20th centuries - in particular those of Panteleimon Kulish, Ivan Levytskyi and Ivan Pului (1905), Ivan Ohiienko (1962), and Ivan Khomenko (1963) - inherited some of the words of the sixteenth- and seventeenth-century "prosta mova" to denote religious and ethical values/anti-values in Gal. 5:19-23, e. g., within the thematic groups of "debauchery",  "apostasy", and "anger/discord". The biblical writtenmonuments of the early modern era laid the foundation for the traditions of Ukrainian Bible translation and paved the way for the formation of the Ukrainian linguistic usage in the field of religious communication.
Keywords: Bible, axiology, ethical catalog, virtue, vice, Krekhiv Apostle, Ostroh Bible, Bible translation, Old Ukrainian